2003
DOI: 10.1097/01.asn.0000054494.85680.1c
|View full text |Cite
|
Sign up to set email alerts
|

Dual Kidneys from Marginal Adult Donors as a Source For Cadaveric Renal Transplantation in the United States

Abstract: Abstract. The current organ shortage has led to the utilization of double kidney transplants from marginal adult donors, but outcomes data are limited. The United Network for Organ Sharing registry database was used to compare the outcomes of 403 dual adult kidney transplantations (DKT) and 11,033 single kidney transplantations (SKT) from 1997 to 2000. Graft and patient survival and the effect of multiple risk factors were evaluated. It was found that DKT patients were older, less sensitized, and received graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 17 publications
1
48
1
3
Order By: Relevance
“…14 Andres and associates 17 and UNOS criteria. 18 However, he did not find any improvement in 12-month eGFR of DKT compared with allocation based on donor eGFR. The only consensus found among centers is the basic of conditions for ECD, which are generally accepted as the starting point for further decision-making.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…14 Andres and associates 17 and UNOS criteria. 18 However, he did not find any improvement in 12-month eGFR of DKT compared with allocation based on donor eGFR. The only consensus found among centers is the basic of conditions for ECD, which are generally accepted as the starting point for further decision-making.…”
Section: Discussionmentioning
confidence: 91%
“…These studies found lower or similar DGF rates after a DKT. 12,17,18 Graft survival after a DKT compared with an SKT at 5 years (69% vs 61%) and 8 years (69.7% vs 59.4%) has been reported as comparable. 28,29 Despite good DKT outcomes, decision-making remains the main dispute.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the United States, patients waiting for kidney transplant now number 50000 with an annual death rate of 6.3%. 1 To increase the number of organs available for transplant, the use of kidneys from donors from age extremes (pediatric or elderly) has been suggested. In late 2003, the United Network for Organ Sharing (UNOS) implemented the use of kidneys from extended criteria donors (ECDs).…”
Section: Introductionmentioning
confidence: 99%